Dampak Metode Pembelajaran PAI terhadap Motivasi Belajar Siswa di SMPN 12 Kota Bengkulu - Rini Fitria; Decky Saputra; Manisa Rasti Amanda Putri; Ratna Khajar; Tiara Puspita Sari (DIDAKTIKA, 2025)
This research aims to analyze the impact of Islamic Religious Education (PAI) learning methods on student learning motivation at SMPN 12 Bengkulu City. The research method used is quantitative research with a descriptive approach. Data was collected through observation, questionnaires and interviews with PAI students and teachers. The research results show that varied learning methods, such as group discussions, interactive lectures, and technology-based approaches, have a positive impact on students' learning motivation. Factors that contribute to increasing learning motivation include active student interaction, teacher involvement in facilitating learning, and the use of innovative learning media. This research concludes that choosing the right learning method in PAI plays a significant role in increasing students' learning motivation.